SICKLY CHILDREN: THE RATIONAL DRUG THERAPY - S.K. Arshba (Педиатрическая фармакология)
The problem of frequent respiratory infections is the most relevant for sickly children. The author stresses that young children and children attending organized child care centers are more prone to acute respiratory diseases. Paper is devoted to prevention and rational treatment of acute respiratory infections in sickly children. Examples of the improper use of the immunomodulating therapies encountered in practice are cited. It is shown that in the absence of specific prevention, the most effective in terms of evidence-based medicine, is an immunomodulator of bacterial origin, particularly ribosomal-proteoglikan complex. Key words: sickly children, acute respiratory infections, prevention, treatment, immunomodulators, ribosomal-proteoglikan complex. (Pediatric Pharmacology. — 2011; 8 (5): 109–112.)